The Analysis of Mantab Habituation in Strengthening the Profile of Pancasila Students of Elementary School Students - Kholilah, Nur Kamelia; Aeni, Kurotul (Jurnal Prima Edukasia, 2025)
Pancasila Student Profile is a standard for students' character and skills, grounded in Pancasila's values, and serves as a framework for achieving national education goals. The purpose of this research is to describe and analyze the implementation of the dimensions of faith, fear of God Almighty, and noble character in habituation activities as part of the implementation of the Pancasila Learner Profile. In addition, this research focuses on identifying the various obstacles that arise and on efforts to resolve them. This research approach refers to the descriptive qualitative method. The data collection process was conducted through interviews, observations, and documentation. The stages of data analysis include information collection, data reduction, data presentation, and drawing conclusions. To test the validity of the data, source triangulation techniques were used to ensure the credibility of the findings. The results of the Pancasila Student Profile research are implemented through programmed routine habituation activities and exemplary routines. Obstacles to its implementation include a lack of evaluation and monitoring, insufficient student understanding, a negative environment, and insufficient student motivation. Solutions to these obstacles are consistent evaluation and monitoring, teacher training, collaboration of principals, teachers, parents, and students, and student motivation. The results of this study contribute to the development of knowledge regarding habit-forming strategies to strengthen the Pancasila Student Profile, as well as providing a practical overview for educators on implementing habit-forming activities in the school environment.